Polish Youngsters as the Area of Research of Father Professor Janusz Mariański - Andrzej Potocki (Nicolaus Copernicus University in Toruń, 2012)
This article is an attempt to systematize the academic research of Fr. Prof. Janusz Mariański, the Chair of the Sociology of Morals at the Department of Sociology of the Catholic University of Lublin (Katedra Socjologii Moralności na Wydziale Socjologii Katolickiego Uniwersytetu Lubelskiego), dedicated to the situation of youngsters in Poland. According to Prof. Mariański, the research area that is especially privileged today, apart from the sociology of religion and the sociology of morals, is the sociology of young people. He is interested in the system of values of the young generation, especially in the context of multi-directional changes that are taking place in the modern Polish society. The centre of Prof. Mariański's academic interests is the moral, religious and social stance of the young people in Poland. He presents their attitudes and viewpoints within numerous conditionings and relationships, while taking into account the works of different sociologists on the subject.